Evaluation of accuracy, exclusivity, limit-of-detection and ease-of-use of LumiraDx: an antigen-detecting point-of-care device for SARS-CoV-2 - Krüger, Lisa; Klein, Julian; Tobian, Frank; Gaeddert, Mary; Lainati, Federica; Klemm, Sarah; Schnitzler, Paul; Bartenschlager, Ralf; Cerikan, Berati; Neufeldt, Christopher; Nikolai, Olga; Lindner, Andreas K.; et al. (Infection, 2022)
Purpose  Rapid antigen-detecting tests (Ag-RDTs) for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) can transform pandemic control. Thus far, sensitivity (≤ 85%) of lateral-flow assays has limited scale-up. Conceivably, microfluidic immunofluorescence Ag-RDTs could increase sensitivity for SARS-CoV-2 detection. - Methods  This multi-centre diagnostic accuracy study investigated performance of the microfluidic immunofluorescence LumiraDx™ assay, enrolling symptomatic and asymptomatic participants with suspected SARS-CoV-2 infection. Participants collected a supervised nasal mid-turbinate (NMT) self-swab for Ag-RDT testing, in addition to a professionally collected nasopharyngeal (NP) swab for routine testing with reverse transcriptase polymerase chain reaction (RT-PCR). Results were compared to calculate sensitivity and specificity. Sub-analyses investigated the results by viral load, symptom presence and duration. An analytical study assessed exclusivity and limit-of-detection (LOD). In addition, we evaluated ease-of-use. - Results  The study was conducted between November 2nd 2020 and 4th of December 2020. 761 participants were enrolled, with 486 participants reporting symptoms on testing day. 120 out of 146 RT-PCR positive cases were detected positive by LumiraDx™, resulting in a sensitivity of 82.2% (95% CI 75.2-87.5%). Specificity was 99.3% (CI 98.3-99.7%). Sensitivity was increased in individuals with viral load ≥ 7 log10 SARS-CoV2 RNA copies/ml (93.8%; CI 86.2-97.3%). Testing against common respiratory commensals and pathogens showed no cross-reactivity and LOD was estimated to be 2-56 PFU/mL. The ease-of-use-assessment was favourable for lower throughput settings. - Conclusion  The LumiraDx™ assay showed excellent analytical sensitivity, exclusivity and clinical specificity with good clinical sensitivity using supervised NMT self-sampling. Trial registration number and registration date  DRKS00021220 and 01.04.2020